Layered Global Player Legal Dynamics of EU External Relations - de Waele, Henri; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Layered Global Player offers a concise but thorough overview of the principles of EU external relations law. By closely examining the role of the European Union on the global scene, it aims to provide a systematic overview of the relevant rules and competences, reflecting the legal developments in their historical and political context. The book contains up-to-date analyses of topics such as the Common Foreign and Security Policy, the Common Security and Defence Policy and the Common Commercial Policy. Moreover, it devotes specific attention to the EU$1 (Bs external powers with regard to the environment, fundamental human rights and development cooperation. It also includes a dedicated chapter exploring the relations with neighbouring countries, as well as one that elucidates the complex interplay between rules of domestic, European and international provenance. Overall, this book couples an innovative design with comprehensive coverage and an engaging style of writing. Its compactness and accessibility enable readers to master the main features of this dynamic field of law with ease, making it an indispensible resource for scholars and practitioners alike.s
Chapter 1: Introducing the layered global player -- Part I Legal dynamics in the outer Layer: Chapter 2: The common foreign and security policy -- Chapter 3: The common security and defence policy -- Part II Legal dynamics of the middle layers: Chapter 4: The common commercial policy -- Chapter 5: The external environmental policy -- Chapter 6: The external human rights policy -- Chapter 7: The development cooperation and humanitarian aid policy -- Part III Legal dynamics in the inner layer: Chapter 8: Special relationships in the European neighbourhood and beyond -- Chapter 9: The EU, the Member States and international law -- Chapter 10: Conclusion: an effective global player?.
Keywords: Law; Public law; Law; European Law/Public International Law